Patient-reported outcomes for monitoring symptomatic toxicities in cancer patients treated with immune-checkpoint inhibitors: A Delphi study. (November 2021) - Da Silva Lopes, André Manuel; Colomer-Lahiguera, Sara; Mederos Alfonso, Nuria; Aedo-Lopez, Veronica; Spurrier-Bernard, Gilliosa; Tolstrup, Lærke Kjær; Pappot, Helle; Aspeslagh, Sandrine; Rogiers, Anne; Neyns, Bart; Haanen, John B.; Mitchell, Sandra A.; et al.
Abstract: Background: Immune-related adverse events (IrAEs) associated with the use of immune checkpoint inhibitors (ICIs) may not be fully covered by existing measures like the PRO-CTCAE™. Selecting PRO-CTCAE™ items for monitoring symptomatic adverse events is hindered by the heterogeneity and complexity of IrAEs, and no standardised selection process exists. We aimed to reach expert consensus on the PRO-CTCAE™ symptom terms relevant for cancer patients receiving ICIs and to gather preliminary expert opinions about additional symptom terms reflecting ICI symptomatic toxicities. Additionally, we gathered expert consensus about a core set of priority symptom terms for prospective surveillance and monitoring. Design: This Delphi study involved an international panel of experts (n = 6 physicians; n = 3 nurses, n = 1 psychiatrist and n = 1 patient advocates). Experts prioritised the relevance and importance of symptom terms to monitor in patients treated with ICIs. Results: Experts reached a consensus on the relevance of all (n = 80) PRO-CTCAE™ Symptom Terms. Consensus on the importance of these symptom terms for prospective monitoring in patients receiving ICIs was reached for 81% (n = 65) of these terms. Additional symptoms terms (n = 56) were identified, with a consensus that 84% (47/56) of these additional symptom terms should also be considered when monitoring symptomatic IrAEs. Conclusion: This study identified a prioritised list of symptom terms for prospective surveillance for symptomatic IrAEs in patients receiving ICI treatment. Our results indicate the need to strengthen the validity of PRO measures used to monitor patients receiving ICIs. While these results provided some support for the content validity of the PRO CTCAE™ and resulted in a preliminary set of salient symptomatic adverse events related to the use of ICIs, broader international agreement and patient involvement are needed to further validate our initial findings. Highlights: Current PRO-CTCAE™ library does not appear to cover the full spectrum of IrAEs. This Delphi prioritised PRO-CTCAE™ terms to address symptomatic IrAEs. Additional 56 new terms were suggested to form the expansion of the current library. Further is needed to guide how ICI toxicity can be approached with PROs.